Perceived Fairness and Consequences of Affirmative Action Policies - Hannah Schildberg-Hörisch; Marco A. Schwarz; Chi Trieu; Jana Willrodt (Center for Economic Studies and ifo Institute (CESifo), 2022)
Debates about affirmative action often revolve around fairness. Accordingly, we document substantial heterogeneity in the fairness perception of various affirmative action policies. But do these differences translate into different consequences? In a laboratory experiment, we study three different quota rules in tournaments that favor individuals whose performance is low, either due to discrimination, low productivity, or choice of a short working time. Affirmative action favoring discriminated individuals is perceived as fairest, followed by that targeting individuals with a short working time, while favoring low productivity individuals is not perceived as fairer than an absence of affirmative action. Higher fairness perceptions coincide with a higher willingness to compete and less retaliation against winners, underlining that fairness perceptions matter for the consequences of affirmative action. No policy harms overall productivity or post-competition teamwork, but affirmative action may reduce the average output of tournament winners.
Keywords: C91; D02; D63; 330; affirmative action; fairness ideals; experiment; tournament; real effort